Theoretical Studies on the Mechanism of Thioesterase-Catalyzed Macrocyclization in Erythromycin Biosynthesis - Chen, Xiong-Ping; Shi, Ting; Wang, Xiao-Lei; Wang, Jitao; Chen, Qihua; Bai, Linquan; Zhao, Yi-Lei (ACS catalysis, 2016)
Macrocyclic polyketides, biosynthesized by modular polyketide synthases (PKSs), have been developed successfully into generation-by-generation pharmaceuticals for numerous therapeutic areas. A great effort has been made experimentally and theoretically to elucidate the biosynthesis mechanisms, in particular for thioesterase (TE)-mediated macrocyclization, which controls the final step in the PKS biosynthesis and determines chemical structures of the final products. To obtain a better insight into the macrocyclization process (i.e., releasing step), we carried out MD simulations, QM and QM/MM calculations on complexes of 6-deoxyerythronolide B synthase (DEBS) TE and two substrates, one toward a macrocyclic product and another toward a linearly hydrolytic product. Our investigation showed the induced-fit mutual recognition between the TE enzyme and substrates: in the case of macrocyclization, a critical hydrogen-bonding network is formed between the enzyme and substrate 1, and a hydrophobic pocket appropriately accommodates the substrate in the lid region, in which a pivotal prereaction state (1 IV′) with an energy barrier of 11.6 kcal/mol was captured on the potential energy surface calculation. Accompanied with the deprotonation of the prereaction state, the nucleophilic attack occurs with a calculated barrier of 9.9 kcal/mol and leads to the charged tetrahedral intermediate. Following the decomposition of the intermediate, the final macrocyclic product releases with a relatively low barrier. However, in the case of hydrolysis, such a prereaction state for cyclization was not observed in similar molecular simulations. These calculations are consistent with the previous biochemical and structural studies about the TE-mediated reactions. Our study indicated that the enzyme–substrate specificity stems from mutual molecular recognition via a prereaction state between DEBS TE and substrates, suggesting a prereaction-and-action mechanism in the TE macrocyclization and release of PKS product.